2014
DOI: 10.1080/14616696.2014.968797
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Intergenerational Transmission of Social Assistance in the Nordic Countries in the 2000s

Abstract: This study considered trends in the intergenerational transmission of social assistance (SA) among young adults in Finland, Norway and Sweden during the 2000s. Comparable administrative register datasets enabled us to compare year by year the social assistance recipiency of 20-year-old adults in the period 1999-2008, together with information on their parents' social assistance recipiency at the time when those young adults were aged 16 years. The intergenerational odds-ratio for SA was stronger in Sweden than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Kauppinen et al () found out that disadvantaged social background was a significant predictor for both short‐ and long‐term spells of social assistance among young adults in Finland. Moreover, previous research has shown signs of intergenerational transmission of social assistance in the Nordic countries (Moisio, Lorentzen, Bäckman, Angelin, Salonen, & Kauppinen, ; Stenberg, ).…”
Section: Life Course and Social Assistance Dynamicsmentioning
confidence: 93%
“…Kauppinen et al () found out that disadvantaged social background was a significant predictor for both short‐ and long‐term spells of social assistance among young adults in Finland. Moreover, previous research has shown signs of intergenerational transmission of social assistance in the Nordic countries (Moisio, Lorentzen, Bäckman, Angelin, Salonen, & Kauppinen, ; Stenberg, ).…”
Section: Life Course and Social Assistance Dynamicsmentioning
confidence: 93%
“…Ringbäck Weitoft et al, 2008;Vauhkonen et al, 2017), and the evidence from the Nordic countries indicates intergenerational transmission of social assistance (e.g. Stenberg, 2000;Moisio et al, 2015). Among young adults, parental social assistance receipt is especially associated with long-term take-up of social assistance (Ilmakunnas and Moisio, 2019).…”
Section: Social Assistance Receipt Across Generationsmentioning
confidence: 99%
“…Ringbäck Weitoft, Hjern, Batljan, and Vinnerljung (2008) compared a large national cohort and related receipt of social assistance at ages 25–26 in 2002 to a number of parental characteristics measured in 1990–1992, including the duration of social assistance receipt. Moisio et al (2015) studied intergenerational relations in social assistance receipt among young adults in Finland, Norway, and Sweden and for different cohorts using data from the end of the 1990s until 2008.…”
Section: Literature Reviewmentioning
confidence: 99%